2017
DOI: 10.1515/sbe-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Decentralization and Delivery of Public Services: Evidence from Education Sector in Pakistan

Abstract: Fiscal Decentralization is the devolution of fiscal assignments to lower governments for high growth and better delivery of public services. The current study covering the period from 1972 to 2009 is an attempt to find out the impacts of fiscal decentralization on public services deliveries in Pakistan. Public services are proxy by Gross enrollment at primary school level while fiscal decentralization by fiscal transfer and expenditure sides of devolution. Using time series data, it is found that the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Conversely, according to Young (1992); " Kim and Lau (1994); Ben and Spiegel (1994)"; Young (1995) TFP growth was result of growth of factor accumulation. But the studies like Romer, andWeil (1992) Islam (1995); Miller and Upadhya (2000) and Rauf et al, (2017) opinioned human capital has significant effect on total factor productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, according to Young (1992); " Kim and Lau (1994); Ben and Spiegel (1994)"; Young (1995) TFP growth was result of growth of factor accumulation. But the studies like Romer, andWeil (1992) Islam (1995); Miller and Upadhya (2000) and Rauf et al, (2017) opinioned human capital has significant effect on total factor productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though the study revealed that teaching quality was not maintained despite the tendency of sub-national governments to increase funds allocated to education, all the same, there was evidence of positive effect on local social needs. Rauf et al (2017) employed annual time series data from 1972-2009 to examine the effect of fiscal decentralization on education sector in Pakistan. Using education as proxy for public service delivery, the study found support for fiscal decentralization theory that devolution of expenditure responsibilities among all levels of government advances public service delivery because school enrollment in Pakistan generally improved as economic regionalization is being implemented.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Fiscal decentralization in Pakistan can lead to promote pro-poor sectors including healthcare reducing poverty in the country (Ahmed, 2013). Fiscal decentralization, in the long run, has positive impacts on the improvement of public services delivery in Pakistan as it has significantly increased the gross enrolment at primary level in the country (Rauf et al, 2017). The 7 th NFC Award supported by the 18 th constitutional amendment in Pakistan has empowered the local governments which may address key national issues like regional inequity and lower social indicators (Nabi & Shaikh, 2010).…”
Section: Introductionmentioning
confidence: 99%